2007
DOI: 10.1177/0894845307300412
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Self-Efficacy, Coping, Career Indecision, and Vocational Choices of Senior High School Students in Greece

Abstract: The main purpose of this study is to examine the dimensions of career indecision among a sample of Greek high school students ( N = 848) and to classify the students of the sample in regard to their career decision status. A second objective is the investigation of the relationship between career decision status groups and generalized self-efficacy, coping strategies, and vocational interests. The results suggest that four factors contribute to career indecision: absence of structure, need for career guidance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
2
32
0
7
Order By: Relevance
“…Indecisive individuals, when making decisions, including in the career domain, face this task with a diminished sense of personal agency. This type of indecision emerged in almost all the studies employing cluster analysis mentioned earlier: undecided/distressed (Rochlen et al, 2004), chronic indecision-impaired development (Rojewski, 1994), undecided (Argyropoulou et al, 2007), anxious undecided individuals (Wanberg & Muchinsky, 1992), neurotic indecisive information seekers (Kelly & Pulver, 2003), decision process inhibitors (Kelly & Lee, 2002), planless avoiders (Larson et al, 1988), indecisive or learning to make decisions (Savickas & Jarjoura, 1991), chronic career indecision (Callanan & Greenhaus, 1992), cluster 1 in the Lucas and Epperson (1990) study, and cluster 4 in Multon et al's (2007) research.…”
Section: Discussionmentioning
confidence: 93%
“…Indecisive individuals, when making decisions, including in the career domain, face this task with a diminished sense of personal agency. This type of indecision emerged in almost all the studies employing cluster analysis mentioned earlier: undecided/distressed (Rochlen et al, 2004), chronic indecision-impaired development (Rojewski, 1994), undecided (Argyropoulou et al, 2007), anxious undecided individuals (Wanberg & Muchinsky, 1992), neurotic indecisive information seekers (Kelly & Pulver, 2003), decision process inhibitors (Kelly & Lee, 2002), planless avoiders (Larson et al, 1988), indecisive or learning to make decisions (Savickas & Jarjoura, 1991), chronic career indecision (Callanan & Greenhaus, 1992), cluster 1 in the Lucas and Epperson (1990) study, and cluster 4 in Multon et al's (2007) research.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, a lower level of self-efficacy denotes a lower level of job satisfaction and a higher level of job stress (Klassen & Chiu, 2010). Career researchers who studied self-efficacy reported that self-efficacy is correlated with job search planning and job search behavior (Fort, Jacquet, & Leroy, 2011), career indecision among high school students (Argyropoulou, Sidiropoulou-Dimakakou, & Besevegis, 2007), and career counseling attitude (Al-Darmaki, 2012). Bandura (1997) suggests that individuals constructed their self-efficacy beliefs from four primary sources: enac-tive mastery experience, vicarious experience, verbal or social persuasion, and physiological and affective state.…”
Section: Introductionmentioning
confidence: 99%
“…Although this measure was published and widely used as a unidimensional scale, evidence has been growing that the CDS has an underlying multidimensional structure that could potentially differentiate between different types of career indecision (Vondracek, Hostetler, Schulenberg, & Shimizu, 1990). Despite concerns regarding whether the CDS should be used as a unidimensional or multidimensional scale (e.g., Vondracek et al, 1990), the CDS is still commonly used in career counseling practices (e.g., Whiston, 2009) and is an interest in research on career indecision (Argyropoulou, Sidiropoulou-Dimakakou, & Besevegis, 2007;Creed, Patton, & Prideaux, 2006;Feldt et al, 2010;Guay, Ratelle, Senecal, Larose, & Deschenes, 2006).…”
mentioning
confidence: 99%